2020
DOI: 10.3390/en13061449
|View full text |Cite
|
Sign up to set email alerts
|

Smart Electrochromic Windows to Enhance Building Energy Efficiency and Visual Comfort

Abstract: Electrochromic systems for smart windows make it possible to enhance energy efficiency in the construction sector, in both residential and tertiary buildings. The dynamic modulation of the spectral properties of a glazing, within the visible and infrared ranges of wavelengths, allows one to adapt the thermal and optical behavior of a glazing to the everchanging conditions of the environment in which the building is located. This allows appropriate control of the penetration of solar radiation within the buildi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
111
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 60 publications
0
111
0
1
Order By: Relevance
“…ncreased cooling demands in modern buildings and automobiles have led to increase in the consumption of energy [1][2][3] . Thus, it is urgent and meaningful to develop new technologies to efficiently modulate the light-heat flow between residences and surrounding environments.…”
mentioning
confidence: 99%
“…ncreased cooling demands in modern buildings and automobiles have led to increase in the consumption of energy [1][2][3] . Thus, it is urgent and meaningful to develop new technologies to efficiently modulate the light-heat flow between residences and surrounding environments.…”
mentioning
confidence: 99%
“…Several studies have recently demonstrated the benefits associated with the building integration of chromogenic devices, mainly ECs [15,78,80,85,89]. Sibilio et al [36] observed that EC devices may allow high energy savings (up to 39-59%, in some cases), but such benefits are indeed influenced by orientation, the control strategy adopted, climatic conditions, and location.…”
Section: Considerations About Building-integration Of Chromogenic Tecmentioning
confidence: 99%
“…Electrochromic devices are devices that can change their optical characteristics such as the degree of transparency, opacity, reflectivity, and color. One of the options for the application of electrochromic devices can be their use as executive elements of "Smart windows" [1]. At the same time, electrochromic devices can be applied in other areas.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the price of electrochromic devices is high [1], and their characteristics are not always stable over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation